2007
DOI: 10.1192/bjp.bp.107.040683
|View full text |Cite
|
Sign up to set email alerts
|

Cluster randomised controlled trial of training practices in reattribution for medically unexplained symptoms

Abstract: Practice-based training in reattribution changed doctor-patient communication without improving outcome of patients with medically unexplained symptoms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
82
0
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 96 publications
(84 citation statements)
references
References 29 publications
(51 reference statements)
0
82
0
2
Order By: Relevance
“…Evidence for the effectiveness of reattribution, however, remains equivocal. Morriss and colleagues (Morriss et al, 2007) found that delivering a reattribution training program to GPs improved doctorpatient communication, but did not improve patient outcomes or service use. While patients reported being more satisfied with the help they received, and more patients endorsed an emotional cause for their symptoms, these associations were not significant (Morriss & Gask, 2002).…”
Section: The Relevance Of Causal Attributions In the Treatment Of Sfdsmentioning
confidence: 98%
See 2 more Smart Citations
“…Evidence for the effectiveness of reattribution, however, remains equivocal. Morriss and colleagues (Morriss et al, 2007) found that delivering a reattribution training program to GPs improved doctorpatient communication, but did not improve patient outcomes or service use. While patients reported being more satisfied with the help they received, and more patients endorsed an emotional cause for their symptoms, these associations were not significant (Morriss & Gask, 2002).…”
Section: The Relevance Of Causal Attributions In the Treatment Of Sfdsmentioning
confidence: 98%
“…However, evidence for the applicability and effectiveness of so-called reattribution therapy, which consists in encouraging patients to relate their symptoms to psychosocial problems (Goldberg et al, 1989), has remained equivocal Larisch et al, 2004;Morriss et al, 2007;Rief et al, 2006). In fact, cognitive behavioural interventions (Kroenke & Swindle, 2000;Kroenke, 2007;Martin et al, 2007b;Stone et al, 2005b), psychodynamic interpersonal therapy (Sattel et al, 2012), and more generally, improved communication between doctors and patients (Aiarzaguena et al, 2007, Henningsen et al, 2007Kirmayer et al, 2004;Peters et al, 2009;Rosendal et al, 2005;Salmon et al, 2004) have been shown to be most effective in the management of SFDs.…”
Section: Clinical Implications: Diagnosis and Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…The two studies providing the most extensive physician training (20-25 hours) resulted in no association between physician training and patients' symptomatology, functioning, or quality of life (Arnold et al, 2009;Rosendal et al, 2007). Three other studies found less intensive physician training programs, 12 hours (Larish et al, 2004) or 1 day or six hours (Morriss et al, 2007) to coincide with no clear improvement in somatization symptomatology; however, Rief and colleagues did find their training to coincide with fewer health care visits for the 6 months subsequent to training .…”
Section: Integrating Cbt Into Primary Carementioning
confidence: 99%
“…Five groups of investigators have reported controlled clinical trials on the effects of such physician training (Arnold et al, 2009;Larish, Schweickhardt, Wirsching, & Fritzsche, 2004;Morriss et al, 2007;Rief, Martin, Rauh, Zech, & Bender, 2006;Rosendal et al, 2007). The two studies providing the most extensive physician training (20-25 hours) resulted in no association between physician training and patients' symptomatology, functioning, or quality of life (Arnold et al, 2009;Rosendal et al, 2007).…”
Section: Integrating Cbt Into Primary Carementioning
confidence: 99%